FORMATION OF THE IMAGE OF THE SERVICE SECTOR ENTERPRISE (Development Service Industry Management, 2024)
In modern conditions of competition, the formation of a positive image of the enterprise becomes a key success factor in any industry in the service sector. A positive image of the enterprise helps to increase its competitiveness, attract new customers and retain old ones, increase the level of trust in the company and increase its revenues.Forming the image of a service enterprise is an extremely important element of its success. The image of the enterprise is determined by the perception of its goods and services by customers, as well as the perception of the company as a whole.   T   The service sector has its own characteristics, as it requires continuous interaction with customers and continuous improvement of service quality to meet their needs and expectations. Creating an image is a matter of strategic planning of the company's activities. An attractive image of the company can work for many years and support the company in difficult circumstances. Therefore, when forming an image, one should rely (mainly) on those concepts and material objects that consumers associate with the eternal values of life. The image of the enterprise is determined by a set of characteristics that give an idea of its activity. For the image, it is not the characteristic itself that is important, but the idea that can be created about it by professional means and which will provide the organization with a positive image.The relevance of research on the topic of image formation of enterprises in the service sector has practical significance, since the results of the research can be used by enterprises to improve their reputation and increase customer satisfaction.In addition, an important aspect of the research is the analysis of trends in image formation in the service sector, in particular, taking into account modern Internet technologies and social networks.It is also relevant to determine the specifics of the formation of the image of enterprises in the service sector, considering their characteristics, for example, an individual approach to each client, quality and efficiency of service, innovation and competitiveness. The article reveals the importance of the image for the enterprise that provides services and its impact on competitiveness and efficiency. The image of the enterprise acts as one of the tools for achieving the strategic goals of the organization, which affect the main aspects of its activity and are oriented towards the future.
Keywords: image; enterprise; service sphere; service sphere enterprise; image formation; positive image of the enterprise